2015
DOI: 10.1002/jaba.224
|View full text |Cite
|
Sign up to set email alerts
|

Using class‐specific compound consequences to teach dictated and printed letter relations to a child with autism

Abstract: The effects of class-specific compound consequences embedded in an identity-matching task to establish arbitrary emergent relations were evaluated. A 3-year-old child with autism was taught identity relations between lowercase letters (Set 1) and uppercase letters (Set 2). A compound stimulus that consisted of an auditory component (dictated letter name) and a visual component (an uppercase letter for Set 1 or lowercase letter for Set 2) followed correct responses. All targeted arbitrary relations emerged (upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
1
11
0
3
Order By: Relevance
“…Os baixos escores no Teste A-C em pelo menos três dos conjuntos de estímulos dos três participantes do presente estudo sugerem a necessidade de se investigar variáveis de procedimento que possam favorecer a emergência dessas relações em indivíduos com autismo. Uma das alternativas poderia ser o uso de consequências específicas (Dube, McIlvane, Maguire, Mackay, & Stoddard, 1989) compostas que incluíssem um componente auditivo (e.g., Varella & de Souza, 2014, 2015; por exemplo, ao escolher corretamente uma palavra impressa no ensino BC-C, além das demais consequências programadas, o experimentador poderia dizer a palavra correspondente à figura e a palavra impressa (cf. Pilgrim, 2011;Varella & de Souza, 2014, 2015.…”
Section: Discussionunclassified
“…Os baixos escores no Teste A-C em pelo menos três dos conjuntos de estímulos dos três participantes do presente estudo sugerem a necessidade de se investigar variáveis de procedimento que possam favorecer a emergência dessas relações em indivíduos com autismo. Uma das alternativas poderia ser o uso de consequências específicas (Dube, McIlvane, Maguire, Mackay, & Stoddard, 1989) compostas que incluíssem um componente auditivo (e.g., Varella & de Souza, 2014, 2015; por exemplo, ao escolher corretamente uma palavra impressa no ensino BC-C, além das demais consequências programadas, o experimentador poderia dizer a palavra correspondente à figura e a palavra impressa (cf. Pilgrim, 2011;Varella & de Souza, 2014, 2015.…”
Section: Discussionunclassified
“…Pairing stimuli with the differential outcomes used in training can therefore be used to add new samples to the stimulus class (see also Dube et al, , Experiment 2). A number of studies have demonstrated that the DOP can be used to facilitate equivalence with individuals with intellectual disabilities and autism spectrum disorder (Joseph et al, ; Varella & De Souza, ). For example, Joseph et al () showed enhanced accuracy in equivalence testing following conditional discrimination training under DOP relative to NDP.…”
Section: Discussionmentioning
confidence: 99%
“…Following that training, the specific reinforcers would become members of the respective classes and thus function as sample and comparison stimuli in test trials. Further, recent research using multielement stimuli as reinforcers shows that each individual element can gain membership in the equivalence classes that are established, thus increasing the number of new relations that derive from the training (Varella & deSouza, 2015).…”
Section: Semantic Repertoires: Contingencies and Equivalence Relationsmentioning
confidence: 98%